What we know about grading : what works, what doesn't, and what's next - Guskey, Thomas R.; Brookhart, Susan M. (ASCD, 2019)
"This comprehensive overview of grading research distills the evidence into meaningful findings and strategies that can be leveraged to improve grading policy and practice"--